Analisis faktor-faktor yang mempengaruhi nasabah memilih bank konvensional dan Bank Syariah di Kota Jambi - Latifa, Eva; Amir, Amri; Hodijah, Siti (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This study (1) to obtain an overview of the characteristics of customers choosing conventional banks and Islamic banks in the city of Jambi. (2) to find out and analyze what factors influence the customer to choose at a conventional bank in the city of Jambi. (3) to find out and analyze what factors influence the customers to choose the Islamic Bank in the City of Jambi.Based on the results of data analysis, (1) Most of the customer respondents chose conventional banks and syaraih banks participating in this study were male sex as many as 97 respondents. Judging from the most recent training, the Diploma was 45 people. The marital status of the most married is 101 respondents.. The income characteristics of 1,000,000-5,000,000 are 63 respondents. The old characteristics of being a customer of 5-10 years as many as 53 respondents. 2) Based on the results of the study that the variables of knowledge, religious, reputation and service have a significant effect on customers choosing conventional banks while products and promotions have no effect on customers choosing conventional banks. (3) Based on the results of research that the product, promotion, religious and reputation variables have a significant effect on customers choosing Islamic banks while knowledge and services have no effect on customers choosing Islamic banks.